An Integrated Circular Intuitionistic Fuzzy MCDM Framework with Radius Operators for Same-Day Delivery Service Selection - Dwi Nurkarimah; Noor Hidayat; Abdul Rouf Alghofari (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The rapid expansion of e-commerce has increased the demand for rapid, reliable, and efficient logistics services, particularly same-day delivery (SDD). Selecting SDD service providers is a multi-criteria decision-making (MCDM) problem because it involves multiple evaluation criteria and expert judgments under uncertainty. This study develops a decision-making framework based on circular intuitionistic fuzzy sets (CIFS) for SDD service selection and evaluates the effect of different CIFS radius operators on ranking outcomes. The proposed methodology is implemented in a case study of SDD service selection in Malang, involving 30 experts, four criteria, and three alternatives. Expert evaluations are aggregated and analyzed using three radius operators: maximum Euclidean distance, radius algebraic product, and radius algebraic sum. A sensitivity analysis is also conducted over the full range of the parameter lambda. The results show that the radius algebraic product operator provides the most stable ranking, consistently producing (AL3 AL2 AL1). These findings indicate that the choice of CIFS radius operator significantly affects decision stability and supports more reliable recommendations.